2000
DOI: 10.2308/aud.2000.19.2.47
|View full text |Cite
|
Sign up to set email alerts
|

Auditor Selection and Audit Committee Characteristics

Abstract: The role of the audit committee in corporate governance is the subject of increasing public and regulatory interest. We focus on one frequently noted function of the audit committee: auditor selection. We argue that independent and active audit committee members demand a high level of audit quality because of concerns about monetary or reputational losses that may result from lawsuits or SEC sanction. Auditors who specialize in the client's industry are expected to provide a higher level of audit quality than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
326
4
18

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(368 citation statements)
references
References 23 publications
20
326
4
18
Order By: Relevance
“…Accounts receivable and income ratio (ACRESAL), inventory and income ratio (INVIN) mobile asset turnover (ACURAST), fixed assets and income ratio (FASINC) are applied to represent sales. Stice (1991);Persons (2011);Fanning et al (1998);Spathis (2002); Abbott and Parker (2000), found that corporate growth opportunities, the value of equity investments, the investment and corporate profitability can effectively help identify fraud. We also apply the Management Expense Ratio (MANEXP), Working Capital Ratio (WORCAP), Fixed Asset Turnover (FASSTU), Mobile Asset Turnover (CURAST), and Cash Flow Ratio (OPECAF) to express companies operating capacity.…”
Section: Variable Selection and Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accounts receivable and income ratio (ACRESAL), inventory and income ratio (INVIN) mobile asset turnover (ACURAST), fixed assets and income ratio (FASINC) are applied to represent sales. Stice (1991);Persons (2011);Fanning et al (1998);Spathis (2002); Abbott and Parker (2000), found that corporate growth opportunities, the value of equity investments, the investment and corporate profitability can effectively help identify fraud. We also apply the Management Expense Ratio (MANEXP), Working Capital Ratio (WORCAP), Fixed Asset Turnover (FASSTU), Mobile Asset Turnover (CURAST), and Cash Flow Ratio (OPECAF) to express companies operating capacity.…”
Section: Variable Selection and Indicationsmentioning
confidence: 99%
“…They found that managers would decrease the company's stock holdings by frequent trading when there is a fraud. Abbott and Parker (2000) exam whether the presence of an independent audit committee effectively reduces the possibility of corporate fraud through a regression. The regression results show when the independent audit committee and corporate annual meetings held at least more than twice, the company have reported to reduce financial reporting errors.…”
Section: Model Developmentsmentioning
confidence: 99%
“…The majority of these studies, mainly of Anglo-Saxon origin, investigate the different factors which affect the efficacy of ACs and usually focus their analysis on listed companies. Different approaches have been used to study AC efficacy, including: (a) linking the ACs considered to be effective with certain corporate characteristics (Menon and Williams 1994;Collier and Gregory 1999;Deli and Gillan 2000;Klein 2002b); (b) determining the most important functions performed by the AC or what features should it have (Kalbers 1992;Kalbers and Fogarty 1993); (c) investigating the relation between the work of the AC and the auditor (Knapp 1987;Abbott and Parker 2000;Raghunandan 2001;Dezoort et al 2003; assessing whether the presence of an AC affects the reliability of financial reporting (Mcmullen 1996;Lin et al 2006;Jaggi and Leung 2007) as well as the extent of voluntary information released by the company (Ho and Wong 2001 and (e) examining whether the specific characteristics of an AC affect its efficacy.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…It was only in 2013 that the establishment of an audit committee was made mandatory for all companies listed on the Amman Stock Exchange (ASE). The inclusion The most effective work of an audit committee is usually seen in terms of directors' connections (Liao and Hsu 2013); risk management (Tao and Hutchinson 2013); quality of reporting (Abbott and Parker 2000;Ruzaidah and Takiah 2004); the quality of audit (Ali 1990); and the selection of external auditors (Mohd Iskandar and Wan Abdullah 2004). Furthermore, only a limited number of studies have examined the effect of the audit committee on a company's performance in developing countries, and even fewer in MENA; most previous studies explored the relationship between diversity on the board and company performance.…”
Section: Introductionmentioning
confidence: 99%